Compatibility of Sleeve Fabric of Tight Alpine Ski Suit with Skin Deformation (Journal of Fiber Bioengineering and Informatics, 2024)
This paper uses a combination of alginate impression and body surface tracing to study the skindeformation mechanism of upper limbs in alpine skiing, and the sleeve pieces were divided into 5regions combined with the characteristics of human heat and sweat. The thickness, permeability andconstant elongation of 7 kinds of elastic fabrics commonly used in tight sports clothing were tested toprovide a quantitative basis for fabric compatibility in different zones. The results showed that the skindeformation in the elbow joint area was significant, the transverse changes were mostly stretching, andthe longitudinal changes were mostly contraction; the characteristics of heat and sweat in upper limbswere distinct, which could be divided into shoulders, upper arms and below the elbow joint; the orderof fabric permeability is as follows: 6>3>7>4>1>2>5, the order of warp tensile elasticmodulus is as follows: 7>6>1>5>2>4, the order of weft tensile elastic modulus is as follows:1>3>7>6>5>2>4; the abc zones of the sleeve are dominated by the demand for air permeability,which is compatible with 3#, 7# and 6# fabrics respectively, the de zones are dominated by the demandfor tensile elasticity, which is compatible with 4# and 2# fabrics respectively.
Keywords: Skin deformation; Tight clothing; Elastic fabric; Structure partition; Alpine skiing.